Closed but provocative questions: curves enclosing unit area - Foster, Colin (Taylor & Francis Group, 2014)
This article describes a task leading to work on curve sketching, simultaneous equations and integration to find the area enclosed between two curves. An initial closed question is used to confront students with a provocative answer, which they then explore in a much more open-ended way.